An Analysis of Deixis in Harry Potter Third Movie “Harry Potter and The Prisoner of Azkaban” Movie Script By J.K. Rowling - Afiya Layansa Zuan; Baiq Suprapti Handini; Siti Ayu Surayya; Muhammad Husnu (CV. ULIL ALBAB CORP, 2024)
The aim of this research is to identify and analyze the different types of deixis using Yule's theory (1996), as well as to determine the function of each deixis found in the main character in the Harry Potter and the Prisoner of Azkaban movie script.The researcher chose this film as the subject of study because it became one of the most popular film in the Harry Potter series and it contains many deictic words. The researcher used a descriptive qualitative method in this study. Reading and note-taking techniques were used to collect the data. The research data is taken from the Harry Potter and the Prisoner of Azkaban movie script (2003). The results of this study show that there are three types of deixis used by Yule's theory (1996), such as person deixis, spatial deixis, and temporal, which are used in the “Harry Potter and the Prisoner of Azkaban movie script”. The function of person-deixis is to point to things and people as possessions, objects, or subjects. The function of spatial deixis is to point out the locations of people, places, and things in an utterance. The function of temporal deixis is to point out the time in an utterance. Furthermore, the researcher found that there are 836 deixis, which consist of 709 deixis of person deixis, 92 deixis of person deixis, and 35 temporal deixis.